Amin Al-Khuli dan Metode Tafsir Sastrawi Atas Al-Qur'an - Ramadhani, Wali (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2017)
This article discusses about the biography of Amin al-Khuli and his thought; literary interpretation of the Quran (TafsirSastrawi). He offers this method because the Quran is Arabic(?arabiyyunmubin). Therefore, the understanding of the Quran can only be revealed by using literary interpretation (tafsirsastrawi). This method has two important studies: the study of the external Quran (dirasah mahawla al-Qur?an) and the study of the internal Quran (dirasah ma fi al-Qur?an)